DISCOURSE COMPETITION IN THE CLASSROOM: POSTSTRUCTURALISM CRITICAL DISCOURSE ANALYSIS ON STUDENT'S SPEECH DURING DISCUSSION - Alfi Syahrin; Ida Nur'aeni; Abdul Wahid (Universitas Negeri Makassar, 2021)
The gender role of a person, whether male or female, depends on the cultural values that develop in the classroom. In the patriarchal class, from the start the gender roles of male students were more dominant than girls, so there was a comparison of gender roles and in turn, men were considered more powerful than women in the class. However, poststructuralism discourse analysis views men's and women's rights equally. This paper reveals that there are differences between male and female students, as seen from the results of the analysis during class discussions. Poststructuralism discourse analysis provides equal rights and research is carried out naturally, without favoritism in learning. The teacher allows the discussion to take place so that it is clear that there is no teacher domination of male and female students.